2006
DOI: 10.1016/s0377-1237(06)80007-9
|View full text |Cite
|
Sign up to set email alerts
|

Secondary and Delayed Bone Grafting in Alveolar and Anterior Palatal Clefts

Abstract: Recreating the bony continuity of the maxillary arch followed by orthodontic correction of dental discrepancies achieves a comprehensive orthosurgical correction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The exact timing of SABG in an individual patient relies on the dental criterion that approximately one-fourth to two-thirds of the root of the permanent canine on the cleft side has been already formed (Boyne and Sands 1972; Abyholm et al, 1981). In spite of widespread popularity of this timing, some authors reported that SABG was performed in their centers later than recommended by Boyne and Sands, that is, between 10 and 12 years (Sindet-Pedersen and Enemark, 1985; Helms et al, 1987) or even after 12 years (Jia et al, 1998; Chowdhury et al, 2006), while in some centers it is often performed earlier—around 5 to 7 years (Ozawa et al, 2007; Precious, 2009; Touzet-Roumazeille et al, 2015; Dissaux et al, 2016) or even at 3 to 4 years (Brudnicki et al, 2017). It follows from this review that the timing of SABG as suggested by Boyne and Sands is not universally accepted.…”
Section: Introductionmentioning
confidence: 99%
“…The exact timing of SABG in an individual patient relies on the dental criterion that approximately one-fourth to two-thirds of the root of the permanent canine on the cleft side has been already formed (Boyne and Sands 1972; Abyholm et al, 1981). In spite of widespread popularity of this timing, some authors reported that SABG was performed in their centers later than recommended by Boyne and Sands, that is, between 10 and 12 years (Sindet-Pedersen and Enemark, 1985; Helms et al, 1987) or even after 12 years (Jia et al, 1998; Chowdhury et al, 2006), while in some centers it is often performed earlier—around 5 to 7 years (Ozawa et al, 2007; Precious, 2009; Touzet-Roumazeille et al, 2015; Dissaux et al, 2016) or even at 3 to 4 years (Brudnicki et al, 2017). It follows from this review that the timing of SABG as suggested by Boyne and Sands is not universally accepted.…”
Section: Introductionmentioning
confidence: 99%